Wind energy development in China: institutional dynamics and policy incentives. (1st January 2002) - Liu, Wen-Qiang; Zhang, Xi-liang; Gan, Lin
China is endowed with rich wind resources. During the early 1990s, China's wind power capacity grew at an average annual rate of 50%. Total installed wind farm capacity reached 344.8 MW by 2000. However, the pace of wind power development has slowed down in recent years. Through economic analysis and identification of the institutional barriers that led to the rise and fall of wind energy development, this paper points out that the development of wind power and large-scale expansion in commercialisation will be directly subject to rationalisation of policies, incentive mechanisms and institutional framework adjustment. It recommends a number of policy incentive changes and an institutional reform.